A Comprehensive Review of Phytonutrients as a Dietary Therapy for Obesity - Siddiqui, Shahida Anusha; Harahap, Iskandar Azmy; Suthar, Priyanka; Wu, Yuan Seng *; Ghosh, Nibedita; Castro-Munoz, Roberto (MDPI, 2023)
Obesity is a complex medical condition mainly caused by eating habits, genetics, lifestyle, and medicine. The present study deals with traditional diets like the Mediterranean diet, Nordic diet, African Heritage diet, Asian diet, and DASH, as these are considered to be sustainable diets for curing obesity. However, the bioavailability of phytonutrients consumed in the diet may vary, depending on several factors such as digestion and absorption of phytonutrients, interaction with other substances, cooking processes, and individual differences. Hence, several phytochemicals, like polyphenols, alkaloids, saponins, terpenoids, etc., have been investigated to assess their efficiencies and safety in the prevention and treatment of obesity. These phytochemicals have anti-obesity effects, mediated via modulation of many pathways, such as decreased lipogenesis, lipid absorption, accelerated lipolysis, energy intake, expenditure, and preadipocyte differentiation and proliferation. Owing to these anti-obesity effects, new food formulations incorporating these phytonutrients were introduced that can be beneficial in reducing the prevalence of obesity and promoting public health.